PROFIL KONDISI FISIK ATLET TAEKWONDO DI DOJANG SPEED TAEKWONDO SCHOOL PELALAWAN - Larasati, Indria; Sulastio, Agus; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to analyze the physical condition profile of taekwondoathletes at Dojang Speed Taekwondo School Pelalawan. Optimal physical condition iscrucial in taekwondo as it supports athletes' performance in competitions, includingaspects of strength, flexibility, endurance, and explosive power. The research methodused is a quantitative descriptive approach with physical tests, including vertical jump,push-ups, sit-ups, flexibility, and the bleep test. The results show that the majority ofathletes, 87.5%, have a physical condition classified as poor, with an average score of3.5 in the range of 2.0-3.9. This indicates that the physical condition of athletes atDojang Speed Taekwondo School Pelalawan still needs improvement. The studyrecommends that coaches design more structured training programs, involve regularevaluations, and pay attention to proper nutrition and recovery to achieve a moreoptimal physical condition. Improving physical condition is expected to enhanceathletes' performance in competitions and minimize the risk of injury.Keywords: Taekwondo, Athlete Physical Test